Language Use, Usage Guides and Linguistic Norms. - Caon, Luisella; Elenbaas, Marion, 1978-; Grijzenhout, Janet (Cambridge Scholars Publisher, 2021)
This volume offers a collection of twelve original papers on language use and attitudes towards language from both a historical and a present-day perspective. The first part of the book focuses on the general theme of language use and on attitudes towards language use in both the past and the present. The second part concentrates on actual language use in personal and public letters from the sixteenth to nineteenth centuries. The third part is mainly concerned with the possible impact of usage guides, and also addresses the problem of language and cultural misunderstanding and the apparent nee.